1993
DOI: 10.1021/bi00081a005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nucleotide binding site of HIV-1 reverse transcriptase using dTTP as a photoaffinity label

Abstract: We have utilized UV-induced cross-linking of [methyl-3H]dTTP to identify the nucleotide binding site on heterodimeric HIV-1 reverse transcriptase (RT). RT was derivatized by irradiating a solution containing [methyl-3H]dTTP and purified recombinant RT for 10 min. The UV-induced cross-linking reaction between dTTP and RT is linear with time of UV exposure up to 10 min, and it has been determined previously that dTTP cross-linking is half-maximal at 90 microM [Cheng, N., Painter, G. R., & Furmann, P.A. (1991) Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The results speak in favour of the localisation of the dNTP binding site and the catalytic center of HIV-RT on the 66 kDa subunit of the heterodimer. These data are in agreement with direct dNTP UV-crosslinking to HIV-RT [8,9], photoaffinity labeling of the enzyme with rlthio UTP [lo], and X-ray analysis data obtained for HIV-RT at 3 A resolution [l 11. (1) enxyme incubated with templatsprimer hybrid, AlFABdCTP for 2.5 min and UV-irradiated for 2.5 min; (2) enzyme incubated for 1 h with template-primer hybrid and AlFABdCIP UV-irradiated before incubation; (3) enzyme irradiated with AlFABdCTP for 2.5 min followed by incubation for 1 h in the presence of template and primer; (4) enzyme irradiated with AlFABdCTP and template followed by addition of primer and incubation for 1 h; (5) enzyme incubated with template, primer and AlFABdCTP, for 2.5 min followed by UV-irradiation for 2.5 min.…”
Section: Resultssupporting
confidence: 81%
“…The results speak in favour of the localisation of the dNTP binding site and the catalytic center of HIV-RT on the 66 kDa subunit of the heterodimer. These data are in agreement with direct dNTP UV-crosslinking to HIV-RT [8,9], photoaffinity labeling of the enzyme with rlthio UTP [lo], and X-ray analysis data obtained for HIV-RT at 3 A resolution [l 11. (1) enxyme incubated with templatsprimer hybrid, AlFABdCTP for 2.5 min and UV-irradiated for 2.5 min; (2) enzyme incubated for 1 h with template-primer hybrid and AlFABdCIP UV-irradiated before incubation; (3) enzyme irradiated with AlFABdCTP for 2.5 min followed by incubation for 1 h in the presence of template and primer; (4) enzyme irradiated with AlFABdCTP and template followed by addition of primer and incubation for 1 h; (5) enzyme incubated with template, primer and AlFABdCTP, for 2.5 min followed by UV-irradiation for 2.5 min.…”
Section: Resultssupporting
confidence: 81%
“…Photo affinity labeling of a binary complex with dTTP resulted in crosslinking to Lys73 (78), and an antibody inhibition study suggested that dNTP binds in the vicinity of residues 65-73 (79). However, the residues implicated by these studies are located on the l3-hairpin that has been proposed, from crystallographic work, to bind to the template strand (Figure 9), and Lys73 is more than 15 A from the primer terminus (10, 11, 37; J Jager, TA Steitz, unpublished).…”
Section: Nucl Eotide Bindingmentioning
confidence: 99%
“…No crystallographic data is currently available of a HIV-1 RT. dNTP complex, but UV-induced crosslinking of labelled dTTP to HIV-1 RT has shown that within the p66 subunit, dTTP appears to cross-link to a single residue, Lys-73 [21]. Thus, the precursor site and the primer-template one are very close in the catalytic subunit of the viral polymerase.…”
Section: Resultsmentioning
confidence: 99%